KEPEMIMPINAN TRANSFORMATIF : PRAKTIK DAN INSTRUMEN SUPERVISI MANAJERIAL PENDIDIKAN DI ERA DIGITAL - Sari, Indah Permata; Rusliani, Lili; Ismalia, Nurul; Azainil; Komariyah, Laili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of digital technology has significantly reshaped educational systems, particularly in the practices and instruments of managerial supervision. Despite this shift, supervisory practices in schools largely remain administrative and have not been fully aligned with data-driven approaches required in the digital era. In this regard, transformational leadership is considered a key driver in facilitating effective, adaptive, and innovative educational management. This study aims to examine managerial supervision practices and instruments through the lens of transformational leadership in the digital context. This research adopts a Systematic Literature Review (SLR) by examining 25 relevant scholarly articles published within the last five years, obtained from Google Scholar and ERIC databases. The analysis followed systematic procedures, including article selection, data extraction, and synthesis, to identify emerging patterns and research gaps.The results indicate that transformational leadership significantly contributes to the shift in managerial supervision from administrative routines to strategic, technology-oriented practices. Furthermore, supervisory instruments have evolved from conventional formats to digital systems that enable more accurate and data-informed decision-making. The study emphasizes that integrating transformational leadership with managerial supervision practices and instruments is essential for improving educational quality in the digital era.